Agrorecreational ecoparks in the quarries territory as a new type of urban production (on the example of Kryvbas) - Rudenko, Taras; Mukha, Tetiana; Rudenko, Mariia (Budownictwo i Architektura / Civil and Architectural Engineering, 2016)
The article analyzes the main conditions of formation of agrorecreational ecoparks in the quarries territory, which no longer perform their initial functions. Agrorecreational ecoparks are regarded as a new type of urban development in combination with recreational function for industrial cities. Thus agrorecreational ecoparks are researched as structural elements of both agroproductive and recreational complexes of a country. Depending on types of activity there have been established main functional subzones and their interposition according to the exploitation mode and territory security. The planning structure of an agrorecreational ecopark locates the subzones of scientific use in the middle of a park, in the most accessible places as they are main attraction for visitors. Natural landscape of recreational use subzone adjoins the scientific zone; service centers and utility zones are located along the edges of the park thus creating a buffer area. The main groups of relief forms have been analyzed, which directly affect the planning structure of the researched parks. The main types of agrorecreational ecoparks in terms of relief forms have been identified; dimensional and spatial peculiarities of organization of such territories have been determined. In the context of a complex terrain and intensive soil erosion the major component of agrorecreational ecoterritories is geoplastic relief with drainage network (columbine), which determines precipitations run-off and the water regime of the park in general. The main notions and special features of landscape columbine and geoplastics (terracing) have been analyzed. The major types of agrolandscapes under the conditions of agrorecreational ecoparks formation have been established.